Potential roles of Culicoides spp. (Culicoides imicola, Culicoides oxystoma) as biological vectors of bluetongue virus in Yuanyang of Yunnan, P. R. China - Li, Nan; Meng, Jinxin; He, Yuwen; Wang, Wenhua; Wang, Jinglin (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Culicoides plays a crucial role as an insect vector in the field of veterinary medicine. The transmission of significant viruses such as bluetongue virus (BTV) and African horse sickness virus (AHSV) by this insect poses a substantial threat, leading to the development of severe diseases in domestic animals. This study aimed to explore the Culicoides species, identify their blood-meal sources, and assess the presence of BTV and AHSV carried by Culicoides in Yuanyang County, Yunnan Province. The aim was to gain insights into the potential vectors of these two viruses and elucidate their potential roles in the transmission of pathogens. Methods The midges were collected from cattle (Bos indicus), pig (Sus scrofa), and goat (Capra hircus) pens in Yuanyang County, Yunnan Province in June 2020. Initial identification of midges was conducted through morphological characteristics, followed by molecular identification using the cytochrome C oxidase subunit I (COI) gene. The determination of Culicoides blood-meal sources was accomplished using specific primers targeting the cytochrome b (Cyt b) gene from potential hosts. BTV and AHSV RNA were identified in Culicoides pools through the application of reverse transcriptase PCR and quantitative real-time PCR. Nucleotide homology and phylogenetic analysis were performed using MegAlign (DNAStar) and Mega 6.0 software. Results A total of 6,300 Culicoides, consisting of C. oxystoma, C. arakawai, C. imicola, and C. innoxius, were collected from cattle, pigs, and goat pens. The engorgement rates for these species were 30.2%, 54.6%, 75%, and 66.7%, respectively. In the cattle pen, the prevailing species is C. oxystoma (100%). In the pig pen, C. arakawai dominates (70%), with C. oxystoma following at 30%. In the goat pen, C. imicola holds the majority (45.45%), trailed by C. oxystoma (25%), C. innoxius (20.45%), and C. arakawai (9.09%). These Culicoides species were identified as feeding on cattle, pigs, goats, chickens (Gallus gallus), and humans (Homo sapiens). The positivity rates for BTV were 20.00% and 11.54% in blood-fed specimens of C. imicola and C. oxystoma, respectively. Conversely, the positivity rates for BTV in non-blood-fed specimens were 0.00% and 6.67% for C. imicola and C. oxystoma, respectively. BTV was not detected in C. arakawai and C. innoxius. The specimens (YY86) from C. imicola that tested positive for BTV had the closest genetic relationship to YTS-4 isolated from Mangshi, Yunnan Province in 1996. All test results for the nucleic acid of AHSV were negative. Conclusion The study reveals variations in the species distribution, community composition, blood sucking rate, and blood-feeding sources of Culicoides across different habitats. Notably, C. imicola and C. oxystoma emerge as potential vectors for the transmission of BTV in local animals. Accordingly, this investigation provides crucial insights that can serve as a valuable reference for the prevention and control of BTV in local animals, particularly from the perspective of vector management.